Linguistic Landscape for Teaching Spatial and Safety-Related Vocabularies to Primary School Students: Integration between Community Service and Teaching - Anna Marietta da Silva; Ignatio Diantama Arinugraha; Li Xinyi; Theodorus Sule; Yanuar Yohana Widarti (Universitas Galuh, 2026)
This community service project (CSP) was conducted in Mita Learning Centre (MLC), a non-profitable learning center in Duren Sawit, East Jakarta. MLC always needs voluntary teachers because it never recruits professionals, but those teachers are not always available on a regular basis, and that motivated this CSP back in 2019. The goal of the 2024 CSP is to introduce an English language learning opportunity in the environment through the adaptation of linguistic landscape in the teaching of English vocabulary in a two-session English tutorial program. This program was integrated to a course called Approaches to English Language Learning in Atma Jaya’s Master’s Program in Applied English Linguistics. The master students (MSTs) who become the English tutors had to design a syllabus based on theories on teaching English vocabulary through linguistic landscape to young learners. After the syllabus was presented in the class, and given feedback from the lecturer, the MSTs conducted the teaching sessions, and then a reflection upon the teaching experiences. Then, the syllabus, the teaching sessions, and the reflection must be reported in the mid and final term-papers. The small survey after the tutorials showed that the pupils in MLC understood the vocabularies taught, enjoyed the learning activities and expected to join the same program in the future.